Linguistic Problem Analysis Of The Song “Count On Me” In An Efl Context - Selviana Napitupulu; Jerico Devaly (CV PUTRA PUBLISHER, 2026)
This study analyzes the motivational impact and linguistic problems arising from the use of the song “Count on Me” by Bruno Mars as instructional material in an Indonesian junior high school EFL classroom. The objectives of this study are to examine students’ learning motivation when songs are integrated into English instruction and to identify linguistic difficulties encountered during the listening activity. The study employed a descriptive qualitative design complemented by quantitative observational data. The qualitative data were obtained from researchers’ classroom observation notes and analysis of students’ responses during guided lyric discussion, which were used to identify linguistic problems at semantic, morphological, syntactic, phonological, and pragmatic levels. The quantitative data were derived from a motivation observation checklist. Students’ motivation was operationalized through four observable indicators: attention, participation, confidence, and anxiety, each scored dichotomously (observed/not observed) and converted into percentages. The learning activity was conducted in a single 80-minute classroom meeting involving 30 eighth-grade students. The findings reveal that the use of the song positively affected students’ motivation, as reflected in high levels of attention and participation, increased confidence, and reduced anxiety. However, students experienced linguistic difficulties, particularly in understanding idiomatic expressions, contractions, phonological reductions, and implicit pragmatic meanings in the song lyrics. This study concludes that while songs function as effective affective tools in EFL instruction, explicit linguistic scaffolding is necessary to ensure meaningful comprehension. Due to the limited duration and single-class implementation, the findings should be interpreted cautiously.